The Use of Titanium Mesh in Guided Bone Regeneration: A Systematic Review - F. Briguglio; D. Falcomatà; S. Marconcini; L. Fiorillo; R. Briguglio; D. Farronato (Hindawi Limited, 2019)
Several techniques have been proposed for bone regeneration in patients with atrophic ridges. Nowadays, GBR represents the gold standard, and it allows obtaining sufficient bone volumes for a correct implant-prosthetic rehabilitation. Our goal is to perform a systematic review of the literature on the use of titanium meshes in GBR in order to evaluate the reliability of the procedure, the regeneration obtained, and the failures. Furthermore, we will evaluate the success and survival rate of the inserted implants. The selected articles concern vertical and/or horizontal regeneration of the alveolar ridge using titanium grids, in association or not with biomaterials, before and simultaneously with implant placement. Six articles were selected for the present review, including a total of 139 patients, 156 sites, and 303 implants. Titanium grids in combination with autogenous bone were used in 2 cases, 5 in combination with a mixture of autogenous bone and bone substitutes. The overall survival and success rates of implants were 98.3% and 85.25%, respectively. In conclusion, our review shows how the use of titanium mesh represented a predictable method for the rehabilitation of complex atrophic sites.